Una nueva especie de Echeveria (Crassulaceae) del estado de Tamaulipas, México - Martínez-Ávalos, José Guadalupe; Mora-Olivo, Arturo (Instituto de Ecología, A.C., 2000)
Echeveria rodolfi is described as a new species from Tamaulipas, Mexico. It was collected in 1998 in an isolated locality of the municipality of Hidalgo near the boundary of the state of Nuevo León. It is compared with E. bifida, E. walpoleana and E. strictiflora, taxa similar in their morphology but, differences in the size of the rosette, in form and size of the leaves, presence of a large number of leaves of wine color, as well as of long pedicels of individual flowers, and the irregular size of bracts and sepals, place E. rodolfi as a new species belonging to the series Angulatae.